Non-Print Information Resources and The Preservation Approaches Recommendation in Tanzanian Academic Libraries - Mubofu, Christian (Department Library of Governance Institut of Home Affairs, 2021)
Background: Non-print information resources are increasingly becoming more important as vital learning materials in higher learning institutions. Academic libraries therefore, have to acquire, process, organize and preserve them for current and future use. Purpose: This paper aims to assess the factors affecting the non-print information resources and their recommended preservation approaches in academic libraries. Method: The study adopted a convergent parallel mixed approach which collects and analyses data to produce integrated findings by using both qualitative and quantitative techniques in a single study. Data was collected by means of questionnaire and in-depth interview. Result: The study revealed that dust, loss of data on disc and hard disc, loss of data due to server failure, high heat, and excessive light, fading of disc surface, high humidity, fungus on disc surface, atmospheric pollutants and virus attack were factors affecting non-print information resources. It was also revealed that highly recommended preservation approaches were good cleanliness of library where information resources are kept, educating library users on how to handle and use information resources, migrating information resources from obsolete storage media to modern storage media, technology preservation and refreshing. Conclusion: The study concludes that library staff need to adopt recommended preservation approaches to safeguard the important information in academic libraries but also system librarians in academic libraries need to be employed to assist in trouble shooting issues. Keywords: Non-Print Information Resources; Information Resources; Information Resources Preservation; Preservation Approaches; Academic Library